2018
DOI: 10.1152/ajplung.00047.2018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Bruton’s tyrosine kinase rescues mice from lethal influenza-induced acute lung injury

Abstract: Infection with seasonal influenza A virus (IAV) leads to lung inflammation and respiratory failure, a main cause of death in influenza-infected patients. Previous experiments in our laboratory indicate that Bruton's tyrosine kinase (Btk) plays a substantial role in regulating inflammation in the respiratory region during acute lung injury in mice; therefore, we sought to determine if blocking Btk activity has a protective effect in the lung during influenza-induced inflammation. The Btk inhibitor ibrutinib (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 31 publications
5
94
1
1
Order By: Relevance
“…Control mice developed respiratory failure, along with histological and computed tomography findings consistent with lung injury, in sharp contrast to the mice that received ibrutinib. 1 Control mice also lost weight and died, whereas those treated with ibrutinib recovered their weight after a brief loss, and all survived. 1 Notably, mice treated with ibrutinib also showed decreased inflammatory cell infiltration, as well as proinflammatory cytokines in lung tissues, that included proinflammatory and chemoattractant cytokines, such as IL-1b, IL-6, KC/CXCL1, TNF-a, and MCP-1, in SARS-Cov-1 and SARS-CoV-2 patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Control mice developed respiratory failure, along with histological and computed tomography findings consistent with lung injury, in sharp contrast to the mice that received ibrutinib. 1 Control mice also lost weight and died, whereas those treated with ibrutinib recovered their weight after a brief loss, and all survived. 1 Notably, mice treated with ibrutinib also showed decreased inflammatory cell infiltration, as well as proinflammatory cytokines in lung tissues, that included proinflammatory and chemoattractant cytokines, such as IL-1b, IL-6, KC/CXCL1, TNF-a, and MCP-1, in SARS-Cov-1 and SARS-CoV-2 patients.…”
mentioning
confidence: 99%
“…The potential for ibrutinib to abrogate pulmonary inflammatory cytokines, lung injury, and death was demonstrated in a highly relevant lethal flu animal model. 1 Therefore, we sought to clarify the impact of ibrutinib in COVID-19 patients. We care for 600 to 800 Waldenstrom macroglobulinemia (WM) patients each year, ;300 of whom are on a BTK inhibitor.…”
mentioning
confidence: 99%
“…Although the effects of Btk signalling on pathogenic microorganism infections are not exactly consented upon, there is no doubt about its importance in maintaining the balance of the immune microenvironment. Many studies have shown that enhanced Btk function plays an important role in inflammatory diseases, such as IAV‐induced acute pneumonia . Therefore, we can control inflammatory processes by regulating Btk activity during different periods of disease to alleviate tissue damage and avoid organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the latest experimental evidence indicates that Btk is involved in influenza A virus (IAV) infection‐associated acute lung injury. Blocking Btk activity reduces weight loss, increases survival and minimizes morphological changes in IAV infection, suggesting that immunomodulatory treatment targeting Btk is an effective approach for controlling influenza‐induced lung injury …”
Section: Btk and Pathogenic Microorganism Infectionsmentioning
confidence: 99%
See 1 more Smart Citation